Mitigasi Banjir Berbasis Masyarakat Pada Desa Rawan Banjir Di Kabupaten Barito Kuala - Deasy Arisanty; Karunia Puji Hastuti; Herry Porda Nugroho Putro; Ersis Warmansyah Abbas; Yohanes Asmardin Halawa; Khairil Anwar (JPG (Jurnal Pendidikan Geografi), 2022)
Sungai Lumbah Village and Bangkit Baru Village are two villages that experienced severe flooding in 2021. The flood events occur every rainy season and high tides. The purpose of this study was to analyze community-based flood mitigation in flood-prone villages, Barito Kuala Regency. The research was carried out in two villages, i.e., Sungai Lumbah Village and Bangkit Baru Village, with a total of 50 informants. The results showed that the pre-flood mitigation carried out by the community was by elevating the rice storage area. The community has never received socialization by the local government regarding flood prevention, but they did it on their own initiative and formed a flood alert team. When there was a flood, they set up a relief center to help the affected people. After the flood, the community cleaned up the flood marks in their respective homes and repaired the damaged agricultural land. Flood management is still carried out on the community's own awareness and is carried out voluntarily.